A preferência de compra de produtos orgânicos considerando diversificação e especialização da agricultura familiar - Alves, Alvaro Guilherme (2023)
Family farming is the backbone of many communities around the world, representing a traditional and sustainable way of producing food. Two strategic paths stand out in this context: specialization, with a focus on and cultivation in specific activities, and diversification, which includes expansion to different agricultural sectors. In this duality, family farming finds ways to optimize resources, increase resilience and meet the constantly evolving demands in the market. The objective of this study was to analyze the preference for purchasing organic products considering the diversification and specialization of family farming in the city of Corbélia-PR. To this end, a survey was carried out through a questionnaire by means of a sample survey. From the study it was possible to identify that taking into account factors that influence consumption habits such as income, health, lifestyle, environment and knowledge when buying organic products, specialization is the most favorable alternative to the producer of organic products, because by being specialized in only one type of production, food has higher quality, being able to meet more specific demands and thus increase their market opportunities.